Comparison of Nasal Cannulas and the OxyArm in Patients Requiring Chronic Domiciliary Oxygen Therapy - James Paul; Ted Otvos (Canadian Respiratory Journal)
OBJECTIVES: The present study was designed to compare the performance of a new oxygen delivery device, the OxyArm (OA) (Southmedic Inc, Canada), with a standard nasal cannula (NC) (Salter-Style 1600, Salter Labs, USA) for both oxygen delivery and patient preference in patients on long-term oxygen therapy (LTOT).